Detectioon And Quantitation Of β-Sitosterol In Diospyros Montana Roxb.Byhptlc - SHRAVAN KUMAR; HAFSA AHMAD; SAKSHI SEHGAL; RAJIV GUPTA; SHUBHINI A. SARAF (International Journal of Pharma and Bio Sciences, 2011)
Diospyros montana Roxb. is a medicinally valued herb in the Ayurvedic and traditional systems of medicine. ß-sitosterol is an important plant sterol present in Diospyros which is reported to posses anti-cancer and adaptogenic properties. In the present study High Performance Thin Layer Chromatography has been developed for detection and quantification of ß-sitosterol in Diospyros montana (leaves, stem bark, roots and seeds).Increasing serial dilutions of reference standard ß-sitosterol (200 to 1000 μg mL-1) were scanned at 273 nm to detect and quantify the concentrations of ß-sitosterol in the test samples. The estimated values obtained from the same were 651.99,467.06,447.14 and 323.87μg mL-1 for leaves, stem bark, roots and seeds respectively. Leaves were found to be the richest source of ß-sitosterol in Diospyros montana Roxb. The method provided a rapid and easy approach for detection and the quantitation of the bio-marker ß-sitosterol. The authors also aim to validate the present method in terms of ruggedness and accuracy and undertake the isolation of ß-sitosterol from the said plant.